The Relationship between Giving 3 Months of Family Planning Injection and Reducing Complaints in Perimenopause at the Penanggal Lumajang Health Center - Sari, Fita Irma; Hikmawati, Nova; Wahyuningsih, Sri (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2024)
Injectable contraception is indeed popular, but unknowingly it has several side effects that can cause a disease if not treated immediately. These side effects include changes in menstrual patterns. In theory, 1 month injection contraceptive acceptors can experience normal menstrual patterns and some can experience changes in menstrual patterns.The purpose of this study was to determine the relationship between giving 3-month family planning injections and reducing perimenopausal complaints at the Penanggal Lumajang Health Center. This research design uses cross sectional. The sampling technique in this study used a total sampling of 30 perimenopausal women at the Pananggal Lumajang Health Center. Measuring tools used in this research are observation sheets and KB cards and questionnaire sheets. This study uses the Spearman rho test. The results showed that the majority of the respondents routinely underwent 3-month injectable family planning as many as 22 respondents (73.3%); the majority of Perimenopausal women experience severe complaints as many as 12 respondents (40%); There is a significant relationship between the administration of 3-month family planning injections and a decrease in perimenopausal complaints at the Penanggal Lumajang Health Center after the Spearman's Rho test was carried out, namely a p-value of 0.000. So it can be concluded that the use of 3-month injectable birth control contraception can affect the reduction of complaints in perimenopausal women. Pibu with 3-month injectable birth control should pay more attention to their health because it can have an impact on decreasing body function.